Huntington's Disease (HD): Degeneration of Select Nuclei, Widespread Occurrence of Neuronal Nuclear and Axonal Inclusions in the Brainstem. (3rd March 2014) - Rüb, Udo; Hentschel, Matthias; Stratmann, Katharina; Brunt, Ewout; Heinsen, Helmut; Seidel, Kay; Bouzrou, Mohamed; Auburger, Georg; Paulson, Henry; Vonsattel, Jean‐Paul; Lange, Herwig; Korf, Horst‐Werner; et al.
Abstract Huntington's disease (HD) is a progressive polyglutamine disease that leads to a severe striatal and layer‐specific neuronal loss in the cerebral neo‐and allocortex. As some of the clinical symptoms (eg, oculomotor dysfunctions) suggested a degeneration of select brainstem nuclei, we performed a systematic investigation of the brainstem of eight clinically diagnosed and genetically confirmed HD patients. This post‐mortem investigation revealed a consistent neuronal loss in the substantia nigra, pontine nuclei, reticulotegmental nucleus of the pons, superior and inferior olives, in the area of the excitatory burst neurons for horizontal saccades, raphe interpositus nucleus and vestibular nuclei. Immunoreactive intranuclear neuronal inclusions were present in all degenerated and apparently spared brainstem nuclei and immunoreactive axonal inclusions were observed in all brainstem fiber tracts of the HD patients. Degeneration of brainstem nuclei can account for a number of less well‐understood clinical HD symptoms (ie, cerebellar, oculomotor and vestibular symptoms), while the formation of axonal aggregates may represent a crucial event in the cascades of pathological events leading to neurodegeneration in HD.